Red mud-fly ash-slag-based foam light soil and preparation method and application thereof

CN123003229APending Publication Date: 2026-10-30RES INST OF HIGHWAY MINIST OF TRANSPORT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611478215.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

(1)激发路径依赖强碱,长期耐久性存在隐患,现有技术中,多数多固废泡沫轻质土体系需额外添加氢氧化钠、生石灰、脱硫石膏等强碱性激发剂,方能有效激活粉煤灰的火山灰活性与矿渣的水硬活性

Benefits of technology

本发明采用赤泥自激发三元协同胶凝泡沫轻质土体系,摒弃了传统碱激发材料对外加强碱激发剂的依赖,充分利用拜耳法赤泥自身携带的弱碱性环境,缓慢持续激发粉煤灰中活性SiO2、Al2O3与矿渣活性组分,并与水泥水化生成的Ca(OH)2反应生成C-S-H凝胶、钙矾石等胶凝产物;同时赤泥中的铁、钙组分参与水化进程并填充孔隙,形成致密稳定的胶凝骨架,在固废总掺量高达90%的条件下,实现800级湿密度对应抗压强度突破2.3MPa,远高于同类高固废泡沫土1.0-1.5MPa的普遍水平,且避免了传统碱激发体系常见的泛碱、界面腐蚀、后期强度倒缩等长期病害,材料的水稳定性、抗冻性及耐候性显著增强,服役寿命大幅延长。此外,均匀分布的封闭泡沫结构使材料干密度仅为传统填料的35%-45%,有效减少地基附加沉降,且微孔结构可释放部分收缩内应力,缓解干燥收缩与温度变形,提升体积稳定性。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of red mud-fly ash-slag-based foam light soil and its preparation method and application, belong to solid waste resource utilization and roadbed engineering material technical field.The material takes bayer process red mud, F class Ⅱ fly ash, S95 grade mineral powder, P·O42.5 grade cement as main cementing component, cooperate with hydroxypropyl methyl cellulose foam stabilizer and a type high molecular composite foaming agent, utilize red mud weak alkaline environment simultaneously stimulate fly ash pozzolanic activity and slag hydraulic activity, realize 90% high solid waste content under the condition of not additional strong alkali activator.Cementing paste is mixed with prefabricated stable foam, and the light backfill material with wet density of 800-1000kg / m 3 Is formed, by adding 0.08%-0.15% silane coupling agent modified basalt short fiber, while keeping 90% solid waste content, the 28d compressive strength of 800kg / m 3 Grade material is increased by more than 70%, the splitting tensile strength is increased by more than 50%, the drying shrinkage strain is reduced by more than 35%, the mechanical properties and frost resistance stability of the material are improved, and the resource recycling of solid waste is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid waste resource utilization and roadbed engineering materials technology, and in particular to a red mud-fly ash-slag based foamed lightweight soil, its preparation method and application. Background Technology

[0002] Currently, the large-scale and high-value utilization of bulk industrial solid waste has become an important development direction in the building materials and road engineering fields. The large-scale stockpiling of industrial solid wastes such as red mud, fly ash, and slag not only occupies valuable land resources but also, due to their alkaline substances and heavy metals, easily leads to environmental problems such as soil alkalization and groundwater pollution, posing a potential threat to the ecological environment. Meanwhile, in road construction, traditional roadbed backfill materials (such as natural crushed stone and pure cement-based materials) generally suffer from technical defects in special conditions such as high embankments for bridge abutments, soft soil foundations in flood detention areas, backfilling around underground pipelines, and road widening. These defects include excessive self-weight leading to differential settlement of the foundation, difficulty in compaction in narrow and irregular spaces, and insufficient water stability and frost resistance, seriously affecting the service quality and lifespan of roads.

[0003] In the field of solid waste resource utilization, preparing foamed lightweight soil from industrial solid waste for roadbed backfilling has become an important way to reduce material weight and dispose of solid waste. While some progress has been made in the research and application of solid waste-based foamed lightweight soil, the following three core defects still hinder its engineering promotion and performance improvement: (1) The activation path depends on strong alkali, which poses a risk to long-term durability. In the existing technology, most solid waste foam lightweight soil systems require the addition of strong alkaline activators such as sodium hydroxide, quicklime, and desulfurized gypsum to effectively activate the pozzolanic activity of fly ash and the hydraulic activity of slag. Although the material strength is improved in the short term, the strong alkaline environment is prone to problems such as efflorescence, pore structure deterioration, and interface corrosion in the later stage, resulting in insufficient long-term durability. At the same time, the introduction of strong alkaline raw materials increases the complexity of construction procedures, on-site operation safety risks, and environmental burden, which is contrary to the green and low-carbon development concept.

[0004] (2) It is difficult to balance the amount of solid waste and the material performance. In the existing single-solid-waste or dual-solid-waste foam lightweight soil system, due to the limited active components, the total amount of solid waste is generally controlled within the range of 30%-80% in order to ensure mechanical properties and durability. The proportion of cementitious components such as cement is relatively high. In the few technical solutions that attempt to increase the amount of solid waste, the proportion of red mud is mostly less than 15%, and the precise proportion and activation mechanism of the ternary synergy of red mud-fly ash-slag have not been formed. Therefore, it is impossible to achieve the unified standard of material mechanical properties, durability and volume stability under the condition of 90% high solid waste content.

[0005] (3) Fiber reinforcement technology has poor adaptability and low reinforcement efficiency. Most existing fiber modification schemes use organic fibers such as polypropylene. These fibers have problems such as weak alkali resistance, easy aging after long-term service, and low elastic modulus, which make it difficult to meet the long-term stability requirements of roadbed backfill materials. A few technical schemes using basalt fibers have weak bonding between fibers and cementitious matrix because they have not carried out surface optimization treatment for the specific hydration products and interface characteristics of the solid waste self-generating system. The fiber content needs to be increased to more than 0.2% to show the reinforcement effect. Moreover, at high content, fiber agglomeration and uneven dispersion are easy to occur, resulting in low reinforcement cost-effectiveness and failing to simultaneously achieve the multiple goals of lightweight, high strength, high toughness and high solid waste disposal.

[0006] In summary, the comprehensive utilization rate of industrial solid waste in road engineering is relatively low. Therefore, developing a foamed lightweight soil material that requires no external alkali activation, can achieve a high solid waste content of 90%, and combines high-performance fiber reinforcement with long-term durability, along with establishing a standardized engineering application scheme to support it, has become an urgent technical requirement for the green and low-carbon transformation of road engineering. Summary of the Invention

[0007] To address the problems existing in the prior art, this invention provides a red mud-fly ash-slag-based foamed lightweight soil, its preparation method, and its application. Utilizing the inherent weak alkalinity of red mud (pH 10.5-11.5), it simultaneously activates the pozzolanic activity of fly ash and the hydraulic activity of slag, achieving stable cementitious performance with a high solid waste content of 90%. Furthermore, it provides a silane coupling agent (KH-550) modified basalt fiber reinforcement scheme adapted to the aforementioned self-activating system. Through a "dry mixing pre-dispersion + interfacial chemical bonding" mechanism, it significantly improves material strength (compressive strength increased by over 70%), crack resistance, and long-term weather resistance under the premise of low admixture content (0.08%-0.15%), without reducing the solid waste content, and without significantly increasing costs.

[0008] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a red mud-fly ash-slag based foamed lightweight soil. By mass percentage, the raw materials consist of the following components: 18%-22% red mud, 36%-40% Class II fly ash (F-grade), 36%-40% S95 grade mineral powder, 8%-12% P·O42.5 grade cement (the sum of the masses of red mud, Class II fly ash, S95 grade mineral powder, and P·O42.5 grade cement is 100%), hydroxypropyl methylcellulose (added at 0.05%-0.10% of the sum of the masses of red mud, Class II fly ash, S95 grade mineral powder, and P·O42.5 grade cement), a type α polymer composite foaming agent, and mixing water. The type α polymer composite foaming agent is diluted with water at a mass ratio of 1:60 to prepare foam, with the foam volume accounting for 35%-55% of the total volume of the foamed lightweight soil, and the water-cement ratio is 0.55. The red mud is Bayer process red mud with a pH value of 10.5-11.5 and a chemical composition including SiO2 13%-14%, Al2O3 14%-15%, Fe2O3 29%-30%, and CaO 14%-15%. It is dried and crushed at 105℃ and passed through a 0.075mm sieve.

[0009] Furthermore, the foam density of the type A polymer composite foaming agent is 48-52 kg / m³. 3 Settling distance ≤ 5mm in 1 hour, water bleeding rate ≤ 25% in 1 hour.

[0010] Furthermore, the mass ratio of the red mud, Class II fly ash (F type), and S95 grade mineral powder is 2:4:4, the cement content is 10% of the total mass of the red mud, Class II fly ash (F type), S95 grade mineral powder, and P·O42.5 grade cement, and the hydroxypropyl methylcellulose content is 0.06% of the total mass of the red mud, Class II fly ash (F type), S95 grade mineral powder, and P·O42.5 grade cement.

[0011] Furthermore, the raw materials of the red mud-fly ash-slag-based foamed lightweight soil also include surface-modified basalt short-cut fibers. The content of surface-modified basalt short-cut fibers is 0.08%-0.15% based on the total mass of the red mud, Class II fly ash, S95 grade mineral powder and P·O42.5 grade cement.

[0012] Furthermore, the amount of surface-modified basalt short-cut fiber is 0.12% of the total mass of the red mud, Class II fly ash (F), Class S95 mineral powder, and P·O42.5 grade cement.

[0013] Furthermore, the length of the surface-modified basalt short-cut fibers is 6-12 mm and the diameter is 13-17 μm.

[0014] Furthermore, the preparation method of the surface-modified basalt short-cut fiber is as follows: basalt short-cut fiber is immersed in a KH-550 silane coupling agent ethanol solution with a mass fraction of 1%-2%, ultrasonically dispersed for 15-20 minutes, taken out, and dried at 105℃ to constant weight to obtain surface-modified basalt short-cut fiber.

[0015] This invention also provides a method for preparing red mud-fly ash-slag based foamed lightweight soil, comprising the following steps: (1) Dry the red mud in an oven at 105℃ to constant weight, crush it and pass it through a 0.075mm sieve; dry the fly ash, mineral powder and cement to a moisture content of ≤1%; if modified basalt fiber is added, dry it to remove impurities to a moisture content of ≤1% and break it up for later use. (2) Immerse the basalt short-cut fibers in a KH-550 silane coupling agent ethanol solution with a mass fraction of 1%-2%, disperse them ultrasonically for 15-20 minutes, take them out, and dry them at 105℃ to constant weight to obtain surface-modified basalt short-cut fibers. (3) Dilute the type A polymer composite foaming agent with water at a dilution ratio of 1:60, and prepare stable foam using a variable frequency foaming machine with a stirring speed of 1200 r / min, a foaming pressure of 20 kPa, and a foam density controlled at 48-52 kg / m³. 3 ; (4) Weigh out red mud, fly ash, mineral powder, cement and hydroxypropyl methylcellulose according to the proportion. If modified basalt fiber is added, weigh out the raw materials at the same time. Put them into the mixer and dry mix at 600 rpm for 3-6 minutes to ensure that the fiber is evenly dispersed and without clumping. Then add the preset amount of mixing water, with a water-cement ratio of 0.55, and stir at 1400 rpm for 5-8 minutes to make a uniform gel slurry. (5) Mixing and molding: Add the prepared foam to the gel slurry in layers. Stir the upper layer at 300 rpm for 2-3 minutes and the lower layer at 300 rpm for 3-6 minutes to ensure that the foam and slurry are mixed evenly. The wet density is controlled at 800-1000 kg / m³. 3 ; (6) Curing: Pour the mixed slurry into the test mold or filling area, cover and cure at a constant temperature of 20℃ for 24 hours, then demold, wrap with a sealed bag or cover with geotextile, and place in a standard curing room to cure to the specified age, with a curing temperature of 20±1℃ and relative humidity ≥95%.

[0016] This invention also provides an application of red mud-fly ash-slag-based foamed lightweight soil in roadbed backfilling projects. The construction adopts a layered filling and self-leveling pouring method. The filling height of each layer is ≤2m, the friction coefficient between filling layers is ≥0.35, the friction coefficient of the contact surface with the bridge abutment foundation is ≥0.40, the construction environment temperature is 5-35℃, and the geotextile is covered for moisture curing for ≥7 days after pouring.

[0017] Furthermore, when the total height of the backfill is ≤8m, the differential settlement is ≤10mm, and the post-construction settlement is ≤30mm.

[0018] Compared with the prior art, the present invention has at least the following advantages and technical effects: This invention employs a red mud self-activated ternary synergistic cementitious foam lightweight soil system, abandoning the reliance on external alkali activators in traditional alkali-activated materials. It fully utilizes the weakly alkaline environment inherent in Bayer process red mud to slowly and continuously activate the active SiO2, Al2O3, and slag active components in fly ash, which react with Ca(OH)2 generated during cement hydration to produce cementitious products such as CSH gel and ettringite. Simultaneously, the iron and calcium components in the red mud participate in the hydration process and fill the pores, forming a dense and stable cementitious skeleton. Under conditions where the total solid waste content is as high as 90%, it achieves a compressive strength exceeding 2.3 MPa corresponding to a wet density of 800, far exceeding the common level of 1.0-1.5 MPa for similar high-solid-waste foamed soils. It also avoids long-term problems common in traditional alkali-activated systems, such as efflorescence, interfacial corrosion, and later strength reduction. The water stability, frost resistance, and weather resistance of the material are significantly enhanced, and its service life is greatly extended. In addition, the uniformly distributed closed foam structure makes the material's dry density only 35%-45% of that of traditional fillers, effectively reducing additional settlement of the foundation. Furthermore, the microporous structure can release some of the shrinkage internal stress, alleviate drying shrinkage and temperature deformation, and improve volume stability.

[0019] To address the common challenge of weak interfacial bonding between basalt fiber and solid waste cementitious matrix, this invention employs a silane coupling agent to modify the surface of basalt fiber, introducing active functional groups onto its surface. One end of these groups forms chemical bonds with the silanol groups on the fiber surface, while the other end forms chemical bonds with hydration products such as CSH gel, significantly improving the fiber-matrix interfacial bonding strength. Only an extremely low dosage of 0.08%-0.15% is required to form a uniform three-dimensional network in the matrix, pinning early-stage hydration microcracks and inhibiting crack initiation and propagation. Under stress, the fiber absorbs a large amount of fracture energy through fiber bridging and pull-out effects, achieving a strength increase of over 70%. This fundamentally improves the brittle characteristics of solid waste cementitious materials while retaining the excellent alkali resistance, weather resistance, and high modulus properties of basalt fiber, making it more suitable for the long-term service environment of roadbeds. Its reinforcement efficiency is far higher than that of unmodified basalt fiber and conventional polypropylene fiber.

[0020] The material of this invention possesses excellent self-leveling properties, allowing it to self-level and fill densely without the need for heavy compaction equipment after pouring. It can conveniently fill narrow, irregularly shaped spaces and complex structural areas. The fiber modification process can be completed simultaneously with the raw material pretreatment, without adding extra construction complexity. Overall construction efficiency is 3-5 times higher than traditional fill materials. In terms of low-carbon economy, this invention significantly reduces cement usage, lowering carbon emissions by 80-100 kg per cubic meter. The solid waste raw materials are widely available and inexpensive. Combined with simplified construction procedures, the overall cost of the foundation system is reduced by 30%-40% compared to traditional materials, while the cost of the fiber-reinforced system increases only slightly. The comprehensive technical and economic benefits are outstanding, providing a practical and feasible technical path for high-value-added disposal of bulk industrial solid waste and promoting the green and low-carbon development of road engineering. Detailed Implementation

[0021] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0022] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0023] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0024] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0025] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0026] This invention provides a red mud-fly ash-slag based foamed lightweight soil. The raw materials, by mass percentage, consist of the following components: 18%-22% red mud, 36%-40% Class II fly ash (F-grade), 36%-40% S95 grade mineral powder, 8%-12% P·O42.5 grade cement (the sum of the masses of red mud, Class II fly ash, S95 grade mineral powder, and P·O42.5 grade cement is 100%), hydroxypropyl methylcellulose (added at 0.05%-0.10% of the sum of the masses of red mud, Class II fly ash, S95 grade mineral powder, and P·O42.5 grade cement), a type α polymer composite foaming agent, and mixing water. The type α polymer composite foaming agent is diluted with water at a mass ratio of 1:60 to prepare foam, with the foam volume accounting for 35%-55% of the total volume of the foamed lightweight soil, and the water-cement ratio is 0.55. The red mud is Bayer process red mud with a pH value of 10.5-11.5 and a chemical composition including SiO2 13%-14%, Al2O3 14%-15%, Fe2O3 29%-30%, and CaO 14%-15%. It is dried and crushed at 105℃ and passed through a 0.075mm sieve.

[0027] In some embodiments of the present invention, the type A polymer composite foaming agent has a foam density of 48-52 kg / m³. 3 Settling distance ≤ 5mm in 1 hour, water bleeding rate ≤ 25% in 1 hour.

[0028] In some embodiments of the present invention, the mass ratio of the red mud, Class II fly ash (F type), and S95 grade mineral powder is 2:4:4, the cement content is 10% of the total mass of the red mud, Class II fly ash (F type), S95 grade mineral powder, and P·O42.5 grade cement, and the hydroxypropyl methylcellulose content is 0.06% of the total mass of the red mud, Class II fly ash (F type), S95 grade mineral powder, and P·O42.5 grade cement.

[0029] In some embodiments of the present invention, the raw materials of the red mud-fly ash-slag-based foamed lightweight soil further include surface-modified basalt short-cut fibers. The content of surface-modified basalt short-cut fibers is 0.08%-0.15% based on the total mass of the red mud, Class II fly ash, S95 grade mineral powder and P·O42.5 grade cement.

[0030] In some embodiments of the present invention, the amount of surface-modified basalt chopped fiber is 0.12% of the total mass of the red mud, Class II fly ash (F), S95 grade mineral powder, and P·O42.5 grade cement, and the amount of hydroxypropyl methylcellulose is 0.06% of the total mass of the red mud, Class II fly ash (F), S95 grade mineral powder, and P·O42.5 grade cement.

[0031] In some embodiments of the present invention, the surface-modified basalt short-cut fibers have a length of 6-12 mm and a diameter of 13-17 μm.

[0032] In some embodiments of the present invention, the preparation method of the surface-modified basalt short-cut fiber is as follows: basalt short-cut fiber is immersed in a KH-550 silane coupling agent ethanol solution with a mass fraction of 1%-2%, ultrasonically dispersed for 15-20 minutes, taken out, and dried at 105°C to constant weight to obtain surface-modified basalt short-cut fiber.

[0033] This invention also provides a method for preparing red mud-fly ash-slag based foamed lightweight soil, comprising the following steps: (1) Dry the red mud in an oven at 105℃ to constant weight, crush it and pass it through a 0.075mm sieve; dry the fly ash, mineral powder and cement to a moisture content of ≤1%; if modified basalt fiber is added, dry it to remove impurities to a moisture content of ≤1% and break it up for later use. (2) Immerse the basalt short-cut fibers in a KH-550 silane coupling agent ethanol solution with a mass fraction of 1%-2%, disperse them ultrasonically for 15-20 minutes, take them out, and dry them at 105℃ to constant weight to obtain surface-modified basalt short-cut fibers. (3) Dilute the type A polymer composite foaming agent with water at a dilution ratio of 1:60, and prepare stable foam using a variable frequency foaming machine with a stirring speed of 1200 r / min, a foaming pressure of 20 kPa, and a foam density controlled at 48-52 kg / m³. 3 ; (4) Weigh out red mud, fly ash, mineral powder, cement and hydroxypropyl methylcellulose according to the proportion. If modified basalt fiber is added, weigh out the raw materials at the same time. Put them into the mixer and dry mix at 600 rpm for 3-6 minutes to ensure that the fiber is evenly dispersed and without clumping. Then add the preset amount of mixing water, with a water-cement ratio of 0.55, and stir at 1400 rpm for 5-8 minutes to make a uniform gel slurry. (5) Mixing and molding: Add the prepared foam to the gel slurry in layers. Stir the upper layer at 300 rpm for 2-3 minutes and the lower layer at 300 rpm for 3-6 minutes to ensure that the foam and slurry are mixed evenly. The wet density is controlled at 800-1000 kg / m³. 3 ; (6) Curing: Pour the mixed slurry into the test mold or filling area, cover and cure at a constant temperature of 20℃ for 24 hours, then demold, wrap with a sealed bag or cover with geotextile, and place in a standard curing room to cure to the specified age, with a curing temperature of 20±1℃ and relative humidity ≥95%.

[0034] This invention also provides an application of red mud-fly ash-slag-based foamed lightweight soil in roadbed backfilling projects. The construction method is layered filling and self-leveling pouring. The filling height of each layer is ≤2m, the friction coefficient between filling layers is ≥0.35, the friction coefficient of the contact surface with the bridge abutment foundation is ≥0.40, the construction environment temperature is 5-35℃, and the geotextile is covered for moisture curing for ≥7 days after pouring.

[0035] In some embodiments of the present invention, when the total height of the backfill is ≤8m, the differential settlement is ≤10mm, and the post-construction settlement is ≤30mm.

[0036] The type A polymer composite foaming agent used in this invention is a polymer composite cement foaming agent from Weihai Zhongsheng New Building Materials Co., Ltd.

[0037] Example 1 A method for preparing red mud-fly ash-slag based foamed lightweight soil includes the following steps: The composition is as follows: 18.2% red mud, 36.3% fly ash, 36.3% mineral powder, and 9.2% cement by mass. 0.06% (calculated based on red mud + fly ash + mineral powder + cement, the same below) of hydroxypropyl methylcellulose is added, with a water-binder ratio of 0.55.

[0038] Step 1: Raw material pretreatment Red mud (Bayer process red mud, pH value 10.5-11.5, chemical composition including SiO2 13%-14%, Al2O3 14%-15%, Fe2O3 29%-30%, CaO 14%-15%) was dried in an oven at 105℃ to constant weight, crushed and passed through a 0.075mm sieve to remove coarse impurities; fly ash, mineral powder and cement were dried to a moisture content ≤1%; basalt fiber was pre-cleaned and dispersed.

[0039] Step 2: Foam Preparation Type A polymer composite foaming agent was diluted with water at a dilution ratio of 1:60, injected into a variable frequency foaming machine, and the stirring speed was set to 1200 r / min and the foaming pressure to 20 kPa to prepare stable foam. Samples were taken to test the foam properties, ensuring a foam density of 48 kg / m³. 3 Settling distance ≤ 5mm in 1 hour, water seepage rate ≤ 25% in 1 hour, and keep on standby after passing the test.

[0040] Step 3: Mixing the gelling slurry Weigh out red mud, fly ash, mineral powder, cement, and hydroxypropyl methylcellulose according to the specified proportions. Simultaneously and slowly add modified basalt fiber to the prepared reinforcing system and put it into a twin-shaft mixer. First, dry mix at 600 rpm for 6 minutes to ensure that the dry materials are mixed evenly and the fiber monofilaments are dispersed without clumping. Then add the preset amount of mixing water (water-cement ratio 0.55) and mix at 1400 rpm for 8 minutes to prepare a uniform, clumping-free gelatinous paste.

[0041] Step 4: Mixing and Molding The prepared foam (55% of the total volume of the foamed lightweight soil) was added to the cementitious slurry in two layers. The upper layer was stirred at 300 rpm for 3 minutes, and the lower layer was stirred at 300 rpm for 6 minutes to ensure that the foam, slurry, and fibers were fully integrated without any foam clumping or stratification. The wet density of the mixed slurry was tested and controlled at 800 kg / m³. 3 The flow rate should be controlled at 200mm. If the parameter deviation exceeds the range, adjust by increasing or decreasing the amount of foam.

[0042] Step 5: Maintenance and Quality Inspection Slowly pour the mixed slurry into the test mold and gently vibrate to remove large air bubbles; after covering and moisturizing for 24 hours in a constant temperature environment of 20℃, demold and wrap with a sealed bag or cover with geotextile and sprinkle with water for curing. Place in a standard curing room (temperature 20±1℃, relative humidity ≥95%) for curing until the specified age.

[0043] 70.7mm×70.7mm×70.7mm specimens were prepared according to specifications. After curing to the specified age, unconfined compressive strength, splitting tensile strength, drying shrinkage strain, water absorption, wet-dry cycle performance, and freeze-thaw cycle performance were tested. The hydration products, pore structure, and fiber interface bonding state were verified by microscopic methods such as XRD and SEM.

[0044] After 28 days of standard curing, the performance test results were as follows: The test was conducted in accordance with the "Technical Specification for Foamed Lightweight Soil for Highways" JTG / T D31-02-2013. The unconfined compressive strength after 28 days was 2.48 MPa, the splitting tensile strength was 0.32 MPa, the water absorption rate was 19.1%, the strength loss rate after 15 wet-dry cycles was 17.2%, the freeze-thaw stability coefficient after 15 freeze-thaw cycles was 0.69, and the total solid waste content was 90%.

[0045] Example 2 The difference from Example 1 is that it includes the following steps: basalt fiber surface modification, preparation of a 1.5% KH-550 silane coupling agent ethanol solution, immersion of basalt short-cut fibers in the solution, ultrasonic dispersion for 20 minutes to make the coupling agent uniformly coat the fiber surface; after removal, drying in an oven at 105℃ to constant weight, cooling and then breaking up for later use.

[0046] In step 3, 0.12% KH-550 modified basalt short-cut fibers (9 mm in length and 15 μm in diameter) were added. The remaining steps were the same as in Example 1.

[0047] After 28 days of standard curing, the performance test results were as follows: the unconfined compressive strength at 28 days was 4.26 MPa, an increase of 71.8% compared to Example 1; the splitting tensile strength was 0.51 MPa, an increase of 59.4%; the drying shrinkage strain was 37.2% lower than that of Example 1; the strength loss rate after 15 wet-dry cycles was 15.8%; the freeze-thaw stability coefficient was 0.71, and there was no long-term performance degradation.

[0048] Example 3 The red mud-fly ash-slag-based foamed lightweight soil prepared in Example 1 was used for bridge abutment backfill construction: 1) Before construction, the foundation pit was cleaned, loose soil and debris were removed, and the contact surface of the bridge abutment foundation was roughened to ensure that the friction coefficient of the contact surface was not less than 0.40; 2) Layered self-leveling pouring was adopted, with a single pouring thickness of 1.2m (to ensure that the filling height of each layer is ≤2m); the material was spread by its own weight without compaction; 3) The ambient temperature of the construction site was controlled at 12-28℃ (within the 5-35℃ construction temperature window); 4) After the single layer was poured, the surface was covered with geotextile for moisture retention and curing for 8 days (≥7 days); after the layer reached the design strength, the next layer was poured; the interlayer roughening treatment was carried out to ensure that the friction coefficient between the filling layers was ≥0.35; 5) After all layers were poured and cured, the subsequent pavement structure layer construction was carried out.

[0049] The abutment backfill structure obtained in this application example has a low overall density, which can significantly reduce the settlement difference between the abutment and the roadbed and effectively alleviate the bridge approach slab settlement problem.

[0050] Comparative Example 1: Unmodified basalt fiber system The difference from Example 1 is that 0.12% of unmodified basalt short-cut fibers are added in step 3, while the rest of the steps are the same as in Example 1.

[0051] After standard curing for 28 days, the performance test results were as follows: the unconfined compressive strength at 28 days was 3.17 MPa, which was 27.8% higher than that of Example 1, but the improvement was only 38.7% of that of the modified fiber; there were obvious gaps at the interface, the fiber pull-out marks were smooth, and the bonding strength was insufficient.

[0052] Comparative Example 2: Polypropylene Fiber System The difference from Example 1 is that 0.12% of chopped polypropylene fibers are added in step 3, while the rest of the steps are the same as in Example 1.

[0053] After 28 days of standard curing, the performance test results showed that the unconfined compressive strength was 3.75 MPa, which was 51.2% higher than that of Example 1. However, the improvement in strength and crack resistance was lower than that of modified basalt fiber. After 90 days of immersion in alkaline solution, the fiber showed signs of aging and embrittlement, with a strength retention rate of only 82% and insufficient long-term stability.

[0054] Comparative Example 3: Binary System Activated by External Strong Base The difference from Example 1 is that the amount of raw materials added is: 30 parts red mud, 60 parts slag, and 10 parts cement, with an additional 3% NaOH added as an activator. The preparation method is the same as in Example 1.

[0055] After 28 days of standard curing, the performance test results were as follows: the unconfined compressive strength after 28 days was 1.87 MPa, the strength loss rate after 15 wet and dry cycles was 26.3%, and obvious efflorescence appeared in the later stage, indicating significant deterioration in durability.

[0056] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A red mud-fly ash-slag based foamed lightweight soil, characterized in that, The raw materials consist of the following components by mass percentage: red mud: 18%-22%, Class II fly ash (F grade): 36%-40%, S95 grade mineral powder: 36%-40%, P·O42.5 grade cement: 8%-12%, with the total mass of red mud, Class II fly ash (F grade), S95 grade mineral powder, and P·O42.5 grade cement being 100%; hydroxypropyl methylcellulose, added at 0.05%-0.10% of the total mass of red mud, Class II fly ash (F grade), S95 grade mineral powder, and P·O42.5 grade cement; type a polymer composite foaming agent; and mixing water. The type a polymer composite foaming agent is diluted with water at a mass ratio of 1:60 to prepare foam, with the foam volume accounting for 35%-55% of the total volume of the foamed lightweight soil, and the water-cement ratio being 0.

55. The red mud is Bayer process red mud with a pH value of 10.5-11.5 and a chemical composition including SiO2: 13%-14%, Al2O3: 14%-15%, Fe2O3: 29%-30%, and CaO: 14%-15%. It is dried and crushed at 105℃ and passed through a 0.075mm sieve.

2. The red mud-fly ash-slag based foamed lightweight soil according to claim 1, characterized in that, The type A polymer composite foaming agent has a foam density of 48-52 kg / m³. 3 Settling distance ≤ 5mm in 1 hour, water bleeding rate ≤ 25% in 1 hour.

3. The red mud-fly ash-slag based foamed lightweight soil according to claim 1, characterized in that, The mass ratio of red mud, Class II fly ash (F type), and S95 grade mineral powder is 2:4:

4. The amount of P·O42.5 grade cement is 10% of the total mass of the red mud, Class II fly ash (F type), S95 grade mineral powder, and P·O42.5 grade cement. The amount of hydroxypropyl methylcellulose is 0.06% of the total mass of the red mud, Class II fly ash (F type), S95 grade mineral powder, and P·O42.5 grade cement.

4. The red mud-fly ash-slag based foamed lightweight soil according to claim 1, characterized in that, The raw materials of the red mud-fly ash-slag-based foamed lightweight soil also include surface-modified basalt short-cut fibers. The content of surface-modified basalt short-cut fibers is 0.08%-0.15% based on the total mass of the red mud, Class II fly ash, S95 grade mineral powder and P·O42.5 grade cement.

5. The red mud-fly ash-slag based foamed lightweight soil according to claim 4, characterized in that, The surface-modified basalt short-cut fibers constitute 0.12% of the total mass of the red mud, Class II fly ash (F grade), S95 grade mineral powder, and P·O42.5 grade cement.

6. The red mud-fly ash-slag based foamed lightweight soil according to claim 4, characterized in that, The surface-modified basalt short-cut fibers have a length of 6-12 mm and a diameter of 13-17 μm.

7. The red mud-fly ash-slag based foamed lightweight soil according to claim 4, characterized in that, The preparation method of the surface-modified basalt short fiber is as follows: basalt short fiber is immersed in a KH-550 silane coupling agent ethanol solution with a mass concentration of 1%-2%, ultrasonically dispersed for 15-20 minutes, taken out, and dried at 105℃ to constant weight to obtain surface-modified basalt short fiber.

8. A method for preparing red mud-fly ash-slag based foamed lightweight soil according to any one of claims 1-7, characterized in that, Includes the following steps: (1) Dry the red mud in an oven at 105℃ to constant weight, crush it and pass it through a 0.075mm sieve; dry the fly ash, mineral powder and cement to a moisture content of ≤1%; if modified basalt fiber is added, dry it to remove impurities to a moisture content of ≤1% and break it up for later use. (2) Immerse the basalt short-cut fibers in a KH-550 silane coupling agent ethanol solution with a mass concentration of 1%-2%, disperse them ultrasonically for 15-20 minutes, take them out, and dry them at 105℃ to constant weight to obtain surface-modified basalt short-cut fibers. (3) Dilute the type A polymer composite foaming agent with water at a dilution ratio of 1:60, and prepare stable foam using a variable frequency foaming machine with a stirring speed of 1200 r / min, a foaming pressure of 20 kPa, and a foam density controlled at 48-52 kg / m³. 3 ; (4) Weigh out red mud, fly ash, mineral powder, cement and hydroxypropyl methylcellulose according to the proportion. If modified basalt fiber is added, weigh out the raw materials at the same time. Put them into the mixer and dry mix at 600 rpm for 3-6 minutes to ensure that the fiber is evenly dispersed and without clumping. Then add the preset amount of mixing water, with a water-cement ratio of 0.55, and stir at 1400 rpm for 5-8 minutes to make a uniform gel slurry. (5) Mixing and molding: Add the prepared foam to the gel slurry in layers. Stir the upper layer at 300 rpm for 2-3 minutes and the lower layer at 300 rpm for 3-6 minutes to ensure that the foam and slurry are mixed evenly. The wet density is controlled at 800-1000 kg / m³. 3 ; (6) Curing: Pour the mixed slurry into the test mold or filling area, cover and cure at a constant temperature of 20℃ for 24 hours, then demold, wrap with a sealed bag or cover with geotextile, and place in a standard curing room to cure to the specified age, with a curing temperature of 20±1℃ and relative humidity ≥95%.

9. The application of red mud-fly ash-slag based foamed lightweight soil as described in any one of claims 1-7 in roadbed backfilling engineering, characterized in that, The construction adopts a layered filling and self-leveling pouring method. The filling height of each layer is ≤2m, the friction coefficient between filling layers is ≥0.35, the friction coefficient of the contact surface with the bridge abutment foundation is ≥0.40, the construction environment temperature is 5-35℃, and the geotextile is covered for moist curing for ≥7 days after pouring.

10. The application according to claim 9, characterized in that, When the total height of the backfill is ≤8m, the differential settlement is ≤10mm, and the post-construction settlement is ≤30mm.